2013
DOI: 10.1186/1479-5868-10-31
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility trial evaluation of a physical activity and screen-viewing course for parents of 6 to 8 year-old children: Teamplay

Abstract: BackgroundMany children spend too much time screen-viewing (watching TV, surfing the internet and playing video games) and do not meet physical activity (PA) guidelines. Parents are important influences on children’s PA and screen-viewing (SV). There is a shortage of parent-focused interventions to change children’s PA and SV.MethodsTeamplay was a two arm individualized randomized controlled feasibility trial. Participants were parents of 6–8 year old children. Intervention participants were invited to attend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 44 publications
2
55
0
Order By: Relevance
“…Three studies employed an intervention specifically to reduce SB,40 44 63 16 studies aimed at increasing PA levels,30 35 36 39 41 46 48 49 55 58–60 64 66 72 78 nine studies combined both approaches of reducing SB and increasing PA levels,32 43 53 62 65 68 70 76 77 one study assessed the effect of a dietary intervention on SB,61 and 22 studies (20 reports) applied a multicomponent lifestyle intervention and observed effects on sedentary behaviour (among other outcomes) 29 33 34 37 38 42 45 47 50–52 54 56 57 67 69 71 73 74 75. Twenty studies offered an alternative intervention,30 36 39–41 45 46 49 52–55 59 61–63 68 72 77 10 studies the usual/routine care,29 37 38 42 50 51 67 71 74 75 seven studies used a waiting list control,29 34 48 64 69 76 78 five studies an attention control,35 44 56 57 60 and control participants of seven studies received no intervention at all 32 33 43 47 58 66 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies employed an intervention specifically to reduce SB,40 44 63 16 studies aimed at increasing PA levels,30 35 36 39 41 46 48 49 55 58–60 64 66 72 78 nine studies combined both approaches of reducing SB and increasing PA levels,32 43 53 62 65 68 70 76 77 one study assessed the effect of a dietary intervention on SB,61 and 22 studies (20 reports) applied a multicomponent lifestyle intervention and observed effects on sedentary behaviour (among other outcomes) 29 33 34 37 38 42 45 47 50–52 54 56 57 67 69 71 73 74 75. Twenty studies offered an alternative intervention,30 36 39–41 45 46 49 52–55 59 61–63 68 72 77 10 studies the usual/routine care,29 37 38 42 50 51 67 71 74 75 seven studies used a waiting list control,29 34 48 64 69 76 78 five studies an attention control,35 44 56 57 60 and control participants of seven studies received no intervention at all 32 33 43 47 58 66 …”
Section: Resultsmentioning
confidence: 99%
“…Twenty-four studies suggested no evidence of a group difference in SB: 10 lifestyle interventions,29 45 50 52 56 57 67 71 73 75 seven PA interventions,35 36 49 55 58 66 72 six PA/SB interventions,53 62 65 70 76 77 and one SB intervention 44. Four studies—two lifestyle,47 69 one PA/SBs,43 one dietary intervention61—did not conclude on SB outcomes despite assessing SB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Power calculations to determine the sample size necessary to detect changes in MVPA are based on previous studies [17,37,38]. Sample sizes are calculated to detect a mean difference of 10 min per day [17,37] of school day MVPA between intervention and control groups at the end of the intervention period. A standard deviation of 12 min [38,39] is used as this value has been reported in the literature when describing the PA patterns in primary school children.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…Family interventions targeting child TV-viewing time typically focus on factors within the family, such as parent knowledge of screen-time recommendations and awareness of strategies to minimize children's electronic media use. [41][42][43] Although this study presents novel data on the potential role of social support in mitigating associations between intrafamilial risk factors and child TV viewing, results should be interpreted cautiously because of a number of study limitations. First, given the use of a cross-sectional design, we cannot determine the temporal ordering of child TV viewing and intrafamilial risk factors.…”
Section: Discussionmentioning
confidence: 93%